2021
DOI: 10.1055/s-0040-1721466
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of Using 8K Ultra-High-Definition Television System for Kasai Portoenterostomy for Biliary Atresia

Abstract: Kasai portoenterostomy (KPE) is currently the first-line treatment for biliary atresia. Many pediatric surgeons have reported that the dissection of the fibrous remnant at the porta hepatis is one of the most important components of this procedure. Furthermore, laparoscopic portoenterostomy is being increasingly used to treat biliary atresia.An advantage of laparoscopic surgery is that surgeons can more easily identify microbiliary ducts, owing to the magnification. We report the case of a 61-day-old girl on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…In clinical experience, 8K UHD images have been reported to provide a high degree of tissue recognition, making it easy to distinguish fine tissue structures and comprehend their morphology 6,7,11 . Colorectal surgery was the most performed surgery in this study.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In clinical experience, 8K UHD images have been reported to provide a high degree of tissue recognition, making it easy to distinguish fine tissue structures and comprehend their morphology 6,7,11 . Colorectal surgery was the most performed surgery in this study.…”
Section: Discussionmentioning
confidence: 83%
“…In clinical experience, 8K UHD images have been reported to provide a high degree of tissue recognition, making it easy to distinguish fine tissue structures and comprehend their morphology. 6,7,11 Colorectal surgery was the most performed surgery in this study. It was reported that autonomic nerves, microvascular networks, and membrane structures were identified as anatomical structures that were more accurately visualized by the 8K UHD images, and identifying these structures accurately could be useful for cancer curability and preservation of organ function in colorectal surgery.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations